Penetapan Kadar Tanin Daun Mangkokan (Polyscias scutellaria (Burm.f.) fosberg) Dan Daun Jambu Biji (Psidium guajava L.) Secara Spektrofotometri UV-Visible - Putri Yupa Hasibuan; Anny Sartika Daulay; Ridwanto Ridwanto; Ainil Fithri Pulungan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Tannins are secondary metabolites belonging to the polyphenol group that exhibit important biological activities, including antioxidant, antibacterial, and anti-inflammatory effects. Mangkokan leaves (Polyscias scutellaria) and guava leaves (Psidium guajava) have long been traditionally used; however, quantitative data regarding their tannin content, particularly in relation to different extraction methods, remain limited. This study aimed to determine total tannin content and identify tannin types in 70% ethanol extracts and infusions of both plants using UV-Vis spectrophotometry. The methodology included phytochemical screening, identification of hydrolyzable and condensed tannins using specific reagents, and quantitative determination of total tannin content using the Folin–Ciocalteu method with gallic acid as a standard. Measurements were carried out at a maximum wavelength of 769 nm, with a regression equation of y = 0.2186x + 0.0024 and a coefficient of determination (R²) of 0.994. The results showed that all samples contained both hydrolyzable and condensed tannins. The highest tannin content was found in the ethanol extract of guava leaves (17.7998 ± 0.0789 mg/g), while the lowest was observed in the infusion of mangkokan leaves (14.0788 ± 0.1986 mg/g). These findings indicate that the type of solvent and extraction method significantly affect tannin yield, with 70% ethanol being more effective than water. In conclusion, both mangkokan and guava leaves have potential as natural sources of tannins, with ethanol extraction providing more optimal results. UV-Vis spectrophotometry proved to be an accurate, sensitive, and reliable method for the quantitative analysis of tannins in plant materials.